2023
DOI: 10.1002/jssc.202300466
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of chemical compositions of three species of Schisandra chinensis by ultra‐high‐performance liquid chromatography quadrupole‐orbitrap‐mass spectrometry

Lexin Shu,
Huixin Qiu,
Shumin Zhang
et al.

Abstract: Schisandra chinensis is a traditional Chinese medicine, which has played an important role in the field of medicine and food. In this study, ultra‐high‐performance liquid chromatography quadrupole‐orbitrap‐mass spectrometry was used to rapidly classify and identify the chemical compositions. Note that 32, 28, and 30 kinds of compounds were successfully identified from northern Schisandra chinensis, vinegar‐processed Schisandra chinensis, and wine‐processed Schisandra chinensis, respectively. The cleavage patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Notably, naringin was considered the only component marker for determining the quality of HJH in ChP, which would negate the unique medicinal and food value of HJH. LC‐MS and HPLC were two efficient methods for determining multi‐components in CMM [44, 45]. Using these two methods, it was found that other ingredients, such as bergapten, isoimperatorin, TCSC, and TCoH, whose content was far inferior to naringin but remarkably more in CGT than in CG, might play a synergistic role in regulating efficacy so that the therapeutic effect of CGT could be more optimized than that of CG.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, naringin was considered the only component marker for determining the quality of HJH in ChP, which would negate the unique medicinal and food value of HJH. LC‐MS and HPLC were two efficient methods for determining multi‐components in CMM [44, 45]. Using these two methods, it was found that other ingredients, such as bergapten, isoimperatorin, TCSC, and TCoH, whose content was far inferior to naringin but remarkably more in CGT than in CG, might play a synergistic role in regulating efficacy so that the therapeutic effect of CGT could be more optimized than that of CG.…”
Section: Discussionmentioning
confidence: 99%
“…MS analysis of metabolites and constituents of TCM is a critical task. However, it generates a large amount of MS data that is difficult to analyze manually [25, 26]. Surprisingly, the emergence of comprehensive computational tools and metabolomic strategies has enabled efficient acceleration of MS data analysis.…”
Section: Introductionmentioning
confidence: 99%